Study of product yields from degraded Meranti Woods for the low temperature pyrolysis process using static batch reactor / Noraishah Othman … [et al.] (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2008)
The pyrolysis of Meranti wood was investigated in a static batch reactor at low pyrolysis temperatures 300°C,350°C and 400 °C. The compositions and properties of the derived gases, pyrolytic oils and solid char were determined with respect to pyrolysis temperature. Preliminary experiment was conducted using thermogravimetric analyzer (TGA) to determine the active range of temperature occurrence during thermal decompositions on the Meranti wood. Different heating rates (20°C/min, 30°C/min and 40°C/min) were applied to look at the effect of heating rate on the wood. The static batch reactor showed that at low temperature, the percentage of char was higher compared to char production at high temperature. Nevertheless, the oil product at low temperature was lower compared to at high temperature and gas production was slightly similar for both conditions. There was a small effect of heating rates on the active pyrolysis rate. All heating rates showed the range of300°C to 400 °C as the active pyrolysis rate.